Annonaceae endémicas del Perú - León, Blanca León (2006)
The Annonaceae include mainly medium to large trees, and are represented in Peru by 27 genera and 236 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004). Here we recognize 44 endemic species in 15 genera. One third of these endemic taxa were described as new to science since 1993, and about 30% only are known from a single botanical collection. Most endemic Annonaceae are found in Very Humid Premontane and Humid Lowland Amazonian Forest regions, between 125 and 2400 m elevation. Ten species are represented within Peru’s protected areas system.